Analysis of Factors Affecting Purchase Decision General Spicy Chips: Analysis of Factors Affecting Purchase Decision General Spicy Chips - Nuning Nurna Dewi (Jurnal Mantik, 2020)
This study aims to determine the effect of product quality, price, brand and promotion on purchasing decisions for spicy general chips at Griyo Taman Asri Wage Sidoarjo. This research was conducted on the decision to purchase spicy general chips with a population of 100 samples. The sampling method with saturated sampling means that the entire population is sampled, ie 100 samples. The data analysis technique used is Multiple Linear Regression Analysis using the SPSS 20.0 for Windows program. Based on the results of data analysis, it was found that prices partially had a positive and significant effect on purchasing decisions. This can be seen from the tcount of 7.131> t table of 1.985 and the significance value of 0.000 <0.05. And partial promotions have no effect on purchasing decisions. This can be seen from the value of tcount of 3.099> t table of 1.985. and a significance value of 0.003> 0.05. Partial brands also have no influence on purchasing decisions. This can be seen from the value of tcount of 1.172 <ttable of 1.985. While product quality has an influence on purchasing decisions. The results of the F test obtained Fcount of 19.751> Ftable of 2.47 and a significance value of 0.204> 0.05. Thus it can be concluded that simultaneously or together the quality of products, prices, brands and promotions can be accepted by statistical tests. From the results of the analysis obtained the coefficient of determination (R2) of 0.454. That is, the four variables of product quality, price, brand and purchasing decisions together contribute 45.4% to purchasing decisions, while the remaining 54.6% is a contribution / contribution to other variables not observed in this study.